DEVELOPMENT OF THE COMPETITIVENESS OF INDUSTRIAL ENTERPRISES IN THE CONTEXT OF A DIGITAL ECONOMY - Mirzayev Shohrux Baxrom o‘g’li, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In the context of the rapid digital transformation of the global economy, industrial enterprises face increasing pressure to remain competitive amid technological disruptions, evolving market demands, and global integration. Competitiveness in today’s environment is no longer limited to cost leadership or operational efficiency; rather, it is defined by an enterprise’s capacity to adopt, integrate, and leverage advanced digital technologies such as artificial intelligence, big data analytics, Internet of Things (IoT), and cloud computing. These technologies enable enterprises to streamline production, enhance product customization, optimize supply chains, and deliver greater value to customers. In this regard, digital transformation becomes not merely an option but a strategic imperative for industrial enterprises aiming to sustain and strengthen their market position. This article investigates the multifaceted factors that influence competitiveness in the digital economy—including technological readiness, innovation capability, digital infrastructure, and workforce digital skills. Furthermore, it proposes a strategic model aimed at fostering digital adaptability and innovation within industrial firms. Finally, the article outlines practical mechanisms and policy recommendations to support effective digital transformation processes across various levels of industrial management.